2010
DOI: 10.1002/ijc.24997
|View full text |Cite
|
Sign up to set email alerts
|

Can physical activity modulate pancreatic cancer risk? a systematic review and meta‐analysis

Abstract: Numerous epidemiological studies have examined the association between physical activity and pancreatic cancer; however, findings from individual cohorts have largely not corroborated a protective effect. Among other plausible mechanisms, physical activity may reduce abdominal fat depots inducing metabolic improvements in glucose tolerance and insulin sensitivity, thereby potentially attenuating pancreatic cancer risk. We performed a systematic review to examine associations between physical activity and pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 67 publications
2
39
0
2
Order By: Relevance
“…According to the Second Expert Report published by the World Cancer Research Fund in 2007, excess body weight increases the risk for developing pancreatic cancer and, therefore, the risk may be decreased by maintaining the weight. Although the results are not consistent, some studies showed an inverse association between physical activity and pancreatic cancer (19,20). Physical activity has been proved to have benefi cial effects on metabolic processes as it decreases glucose levels, increases utilization of glucose in the organism, affects lipid profi le, positively infl uences blood pressure and reduces the amount of body fat.…”
Section: Discussionmentioning
confidence: 98%
“…According to the Second Expert Report published by the World Cancer Research Fund in 2007, excess body weight increases the risk for developing pancreatic cancer and, therefore, the risk may be decreased by maintaining the weight. Although the results are not consistent, some studies showed an inverse association between physical activity and pancreatic cancer (19,20). Physical activity has been proved to have benefi cial effects on metabolic processes as it decreases glucose levels, increases utilization of glucose in the organism, affects lipid profi le, positively infl uences blood pressure and reduces the amount of body fat.…”
Section: Discussionmentioning
confidence: 98%
“…Controls who choose to participate in research studies tend to be more healthy, have a different distribution of LTPA and, therefore, may cause an overinflation in the risk estimate. This meta-analysis was strengthened by the large number of studies included, allowing for extensive subgroup analysis to characterize various subgroups of interest and examine potential (19,20,26). Furthermore, from a methodologic perspective, many studies do not include any or adequate measures of occupational, household-and transportation-related activity, therefore, there is an increased potential for publication bias or gaps in this literature when examining total physical activity in comparison to LTPA.…”
Section: Discussionmentioning
confidence: 99%
“…The body of literature examining the association between physical activity and other cancer sites, including pancreatic cancer (15,18), continues to expand. Previous metaanalyses by Bao and colleagues (19) and O'Rorke and colleagues (20) suggested a possible protective effect of occupational physical activity on pancreatic cancer incidence [relative risk (RR), 0.75; 95% confidence interval (CI), 0.58-0.96 and RR, 0.75; 95% CI, 0.59-0.96, respectively]. However, they reported lack of evidence to support leisure time physical activity (LTPA) in pancreatic cancer risk reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, circulating levels of adiponectin, an adipocyte-secreted hormone with insulin sensitizing and anti-inflammatory properties, has been revealed to be inversely correlated with pancreatic cancer risk, independent of other risk factors (25). Notably, meta-analyses of other anthropometric measures such as physical activity have primarily produced non-significant findings in relation to protective effects against pancreatic cancer (26)(27)(28) (28).…”
Section: Metabolic Syndrome and Pancreatic Cancer Riskmentioning
confidence: 99%